2012
DOI: 10.4012/dmj.2011-189
|View full text |Cite
|
Sign up to set email alerts
|

Initial attachment of human oral keratinocytes cultured on zirconia or titanium

Abstract: Initial attachment of human oral keratinocytes (HOKs) cultured on mirror-surfaced commercially pure titanium (Ti) or yttriastabilized tetragonal zirconia polycrystals (TZP) was investigated. Numbers of viable attached HOKs, their mRNAs and proteins expression of laminin γ2 and integrin β4 were evaluated using the WST-1 assay, quantitative real-time PCR and enzyme-linked immunosorbent assay, respectively. Localization of laminin γ2 and integrin β4 was observed using immunofluorescent staining. Cell spreading wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…No significant difference was observed for integrin β 4 mRNA expression among the specimens and polystyrene at 3 or 24 hours (Figure ). When human oral keratinocytes were investigated, cells cultured on Ti for 1 hour showed a significantly higher laminin γ 2 mRNA expression compared with cells cultured on zirconia . The difference in the cell type used might explain the different results observed.…”
Section: Discussionmentioning
confidence: 98%
“…No significant difference was observed for integrin β 4 mRNA expression among the specimens and polystyrene at 3 or 24 hours (Figure ). When human oral keratinocytes were investigated, cells cultured on Ti for 1 hour showed a significantly higher laminin γ 2 mRNA expression compared with cells cultured on zirconia . The difference in the cell type used might explain the different results observed.…”
Section: Discussionmentioning
confidence: 98%
“…Besides hydrophilicity, keratinocytes and fibroblasts have been found to respond to surface characteristics such as surface chemistry [96, 97] and surface topography [78, 98]. In a study that controlled surface roughness and surface wettability to isolate the effects of surface chemistry on mouse fibroblasts, Ti surfaces that were coated with TiN by physical vapor deposition were compared to surfaces that were either thermally oxidized, laser irradiated or unmodified controls [97].…”
Section: Impact Of Wettability: In Vitro and In Vivo Studiesmentioning
confidence: 99%
“…Atsuta et al showed that peri-implant epithelium (PIE) attaches to a Ti surface by hemidesmosomes with elucidating the localization of laminin γ 2 at the implant-epithelium interface 7,8) . On TZP with a mirror-polished surface, it is reported that the initial attachment of human oral keratinocytes is equivalent to or slightly lower than that on Ti 9) . Accordingly, surface modification of zirconia is necessary to ensure biological sealing around TZP implants.…”
Section: Introductionmentioning
confidence: 99%